Analysis of Behavioral Factors, Use of Gauze, and House Index with The Incidence of DHF in District Dringu Probolinggo - Hikmawan Suryanto (JURNAL KESEHATAN LINGKUNGAN, 2018)
Dengue Haemorrhagic Fever (DHF) is a contagious disease that is still a public health problem in Indonesia. The purpose of this study was to analyze factors associated with the incidence of dengue fever in the district Dringu Probolinggo. This study was an observational study with cross sectional study design. Sampling was done using cluster random sampling with multistage cluster random sampling method. The results showed that there are four variables related to the incidence of dengue that respondents' knowledge about the incidence of dengue (p = 0.004), the action of the respondents on the prevention of dengue (p = 0.025), the use of gauze on ventilation (p = 0.035), and the presence of larvae at home respondents (p = 0.044). Knowledge of the respondents have been good, but there are some that are still lacking so it is necessary to increase the respondents' knowledge about dengue fever. DBD has a good precaution, but there were respondents who still has a moderate value. The use of gauze on the ventilation is still lacking. Lack of use of gauze on ventilation due to ignorance of respondents with benefits gauze. Public Health Center (PHC) and Health Department should improve socialization activities such as outreach to increase public knowledge about the incidence of dengue in order to reduce the number of dengue incidence.